STRENGTHENING RELIGIOUS MODERATION THROUGH PANCASILA-BASED CHARACTER EDUCATION - Anisa Nabilla Firdausi; Alif Ma'fudin (Tahta Media Group, 2025)
This study aims to analyze the implementation and supporting and inhibiting factors of strengthening religious moderation through Pancasila-based character education in students of the Islamic Religious Education S1 Study Program at Darul Ulum Islamic Center Sudirman University. The research uses a qualitative approach with a case study design and a socio-legal approach. Data was obtained through in-depth interviews, lecture observations, focus group discussions, and analysis of curriculum documents and Semester Learning Plans. The results of the study show that the integration of Pancasila values in the curriculum, dialogical pedagogical approaches, community service activities, and strengthening digital literacy are the main factors in strengthening students' religious moderation. An inclusive academic culture and lecturer role models also support the internalization of the values of tolerance and national commitment. However, the limitations of the character evaluation system that are not yet longitudinal, the variation in lecturers' pedagogical competencies, and the challenges of digital polarization are obstacles that need to be overcome. This study concludes that Pancasila-based character education has strategic potential in forming prospective religious educators who are moderate and inclusive, noting that it is necessary to strengthen a more systematic assessment system and digital literacy strategy for the sustainability of long-term impacts.